2021
DOI: 10.3390/ma14154250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Toxicity of Pristine Graphene and Graphene Oxide, Using Four Biological Models

Abstract: There are numerous applications of graphene in biomedicine and they can be classified into several main areas: delivery systems, sensors, tissue engineering and biological agents. The growing biomedical field of applications of graphene and its derivates raises questions regarding their toxicity. We will demonstrate an analysis of the toxicity of two forms of graphene using four various biological models: zebrafish (Danio rerio) embryo, duckweed (Lemna minor), human HS-5 cells and bacteria (Staphylococcus aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…The GO nanocarrier system has more advantages than the traditional anti-tumor drug delivery system, like liposomes. These include ① good blood compatibility and optimal dispersibility in the liquid environment of the human body (53); ② large specific surface area facilitating multi-functional modification by biomolecules and small molecules, such as proteins and single-stranded DNA bases (54); ③ single atomic layer of thickness, and an ultra-high drug loading capacity compared with other nanomaterials (55); ④ sustained release and prolonged drug half-life (56); ⑤ relatively good biological safety and acceptable toxicity (57)(58)(59)(60)(61). Various modification methods have been employed to improve the solubility, stability, and cytotoxicity of GO, while there is still a need to further evaluate the biocompatibility and toxicity of GO nanocarriers into the human body (57,62).…”
Section: Graphene Oxide Nanocarriersmentioning
confidence: 99%
“…The GO nanocarrier system has more advantages than the traditional anti-tumor drug delivery system, like liposomes. These include ① good blood compatibility and optimal dispersibility in the liquid environment of the human body (53); ② large specific surface area facilitating multi-functional modification by biomolecules and small molecules, such as proteins and single-stranded DNA bases (54); ③ single atomic layer of thickness, and an ultra-high drug loading capacity compared with other nanomaterials (55); ④ sustained release and prolonged drug half-life (56); ⑤ relatively good biological safety and acceptable toxicity (57)(58)(59)(60)(61). Various modification methods have been employed to improve the solubility, stability, and cytotoxicity of GO, while there is still a need to further evaluate the biocompatibility and toxicity of GO nanocarriers into the human body (57,62).…”
Section: Graphene Oxide Nanocarriersmentioning
confidence: 99%
“…In zebrafish, the number of unhatched embryos increased, as well as the rate of developmental abnormalities, tail malformations, or pericardial edema. The concentrations of 50 and 100 μg/mL of both CNPs led to the death and coagulation of the embryos; therefore, the survival rate decreased [ 68 ]. The results of Chen et al support the conclusions of the mentioned studies on the embryotoxicity of GO.…”
Section: Developmental Carbon Nanotoxicitymentioning
confidence: 99%
“…Also, graphene administered to the breeding medium is non-toxic at a level below 10 μg / L. 23 Studies of relatively high biocompatibility of GO have also been confirmed by us in experiments on rats, 24 , 25 3D skin model 26 and in studies on other biological models. 27 It seems that GO, as a super-thin layer of carbon applied in a small amount, can, without inducing toxicity, deposit on its surface CS-related proteins present in the body. The use of such anti-inflammatory therapy could significantly reduce the dangerous, further consequences of COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%